Sustainable Food Security Through Innovative Plant-Based Nuggets Enriched with Bamboo Shoots and Moringa: Sensory Acceptance and Nutritional Analysis - Palal, Nor Hairul; Jelani , Muhammad Akmal; Azra , Jeallyza Muthia (Tropical Scientific Journal, 2026)
Objective: This study focuses on developing V-Nutrishoots, a plant-based nugget formulated with Textured Vegetable Protein (TVP) and enriched with bamboo shoots and moringa leaves. Research Method: The development process consisted of three phases: product formulation, sensory evaluation, and nutritional analysis. Three formulations were developed with varying proportions of TVP and bamboo shoots, followed by a sensory evaluation by 35 untrained panelists who assessed color, aroma, taste, texture, juiciness, and overall acceptance, selecting F3 (32% TVP, 64% Bamboo Shoots & 4% Moringa) as the most preferred formulation. The nutritional analysis conducted at Johor Toyyiban Lab revealed that per 100 g, Findings: V-Nutrishoots contained 134 kcal, 2.2 g total fat, 22 g total carbohydrates, and 26.5 g protein. A comparison with existing market products showed that V-Nutrishoots had superior nutritional benefits, with significantly lower calories (134 kcal vs. 250-335 kcal) and higher protein content (26.5 g vs. 12.1-12.5 g) while maintaining a low-fat content (2.2 g vs. 14-17.2 g). Originality: V-Nutrishoots is a healthier alternative to traditional chicken and other plant-based nuggets. To support lifelong learning in food innovation and nutrition, further research should explore antioxidant properties and conduct Texture Profile Analysis (TPA) to assess product quality and functionality